Network structure and pricing in the FX market - Hasbrouck, Joel; Levich, Richard M. (Journal of Financial Economics, 2021)
We construct the network, centrality measures, and attributions of trading profits for a sample of CLS Bank settlement data that spans diverse currency pairs, participants, and execution platforms. We define an average centrality differential as the return to the more-central counterparty in the trade. Estimates imply that the more-central counterparty receives a higher return, and that this differential increases as the counterparties’ centralities diverge. These two results are consistent with a pervasive centrality premium. This premium may reflect bargaining power, but we also find evidence that the premium is partially offset by losses that central agents incur in supplying liquidity.